Embroidery Product Characteristics Analysis Based on Customer Satisfaction as a Trial Project for Empowering SMEs in East Java (Case Study in Embroidery SMEs in Sidoarjo) - Surjanti, Jun; Budiono, Agung Priyo; Endang K, Anneke; Batan, I Made Londen (The International Journal of Accounting and Business Society, 2009)
Sidoarjo has been known as the center of SMEs. As for embroidery product, price variable is the most dominant variable. The research that will be conducted  in based on the previous research that has been conducted by the researchers regarding the customer perception of the characteristics of embroidery product. This research in an exploratory research. The research method that will be used is qualitative  descriptive which will be quantified by Quality Function Deployment (QFD) Method. The subject of this research  is customers, embroidery experts, and TTG experts. The results of the survey consist of data regarding the customer expectation on embroidery product in 4 (four) embroidery outlets in Sidoarjo. The data collected is arranged into the customer quality demand which subsequently comprised into the construct of quality performance. Afterward, the data is processed using WELCOME program and applied into an electric embroidery machine which could produce formatted embroidery pattern. Embroidery patterns that are desired by customers are flowery type such jasmine, rose, cherry blossom, and Kamboja with size in a range of 1-3 cm, which is located in a variety of places, using KESET technique, and modified into 2 dimension with beads, and the color that is preferred in secondary color such as orange, violet, and green, and the type of fabrics that is favored is cotton. In term of the technological capability that is possessed by the crafter, all  demand for the customer  quality construct can be satisfied. This is possible because a meeting regarding the capability and competence of the crafter has been arranged before the survey  was conducted. All crafter that is surveyed in embroidery pattern  and process is still manual without the use of computerized machine with embroidery pattern software. Key words: embroidery, QFD, customer satisfaction, and Sidoarjo.